Strategic Management of Restaurant Business in the Digital Era - Thainphet, Apichaya; Polyorat, Kawpong (Journal for Strategy and Enterprise Competitiveness, 2025)
This article aims to provide guidelines for strategic planning of restaurant businesses for communication in the digital age. By studying from textbooks, books and related academic articles. Then conclude with a descriptive analysis. The results of the study found that the restaurant business plays a vital role in Thailand's economy and has the potential for continued growth. In the current era, digital media has significantly influenced business operations, making it essential for restaurant businesses to focus on appropriate strategic management processes. This ensures adaptability and preparation for changes brought about by digital media. The strategic planning process consists of four steps: 1) analyzing the business environment, 2) formulating strategies, 3) implementing strategies, and 4) evaluating results. The analysis of the business environment is conducted to understand the competitive strengths and weaknesses. This analysis helps determine areas of advantage or disadvantage. Following this, the formulation of strategies becomes a critical step in guiding the business toward its goals. The next phase involves implementing these strategies, where executives must align operational plans with the strategies to achieve the business objectives and enhance competitive potential. Finally, the process concludes with evaluation and control, which measure the success of strategy implementation. Therefore, restaurant businesses should recognize the importance of strategic management processes, as these can bring significant benefits to the business and enhance its competitive efficiency in the digital communication era.